Dream as a Narrative Strategy in Selected Classical Malay Texts - Wan Razali, Wan Roshazli (Malay Literature, 2022)
This paper discusses dream as a narrative strategy in selected classical Malay texts. The discussion covers six Malay historiographical texts: Sulalatus Salatin, Hikayat Raja-raja Pasai, Hikayat Banjar, Tuhfat Al-Nafis, Babad Tanah Jawa and Syair Peperangan Aceh. Mieke Bal’s narrative theory (2017) is used as the main method of discussion. In her book, Narratology: Introduction to the Theory of Narrative (2017), Bal presents 12 important characteristics in narrative theory; event, character, time, location, plot, repetition, focalization, text, author, description, narrative stages and ideology. Based on the analysis, the characteristics can be condensed into five categories: text (theme, point of view, repetition, description, narrative stages, plot, and focalization), author, setting (time, place, and event), ideology and character. However, the discussion of this paper uses one element only, which is the author’s ideology. The findings intend to show the author’s ideology in using dream as one of the narrative strategies to highlight the sovereignty and veneration of the Malay kings. The study’s results prove that dream was used as a narrative strategy by the past royal court authors.